Analisis Faktor Kesuksesan Berwirausaha pada Usaha Mikro dan Kecil di Kota Makassar - Diputra, Indra; Amir, Muhammad; Ramadhina, Annisa; Kasman, Aswar (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study aims to examine the effect of Personality Traits Dimensions, consisting of five variables: Openness, Emotional Stability, Conscientiousness, Agreeableness, Extraversion, on entrepreneurial success. The researcher developed a structural model to test 5 hypotheses within the model. The data were analyzed multivariately using Structural Equation Modeling (SEM) with confirmatory factor analysis. The sample for this study included micro and small enterprises (MSEs) in Makassar city, totaling 342 MSEs. The results show that the ability of the five independent variables within the personality dimensions to influence entrepreneurial success is 17.7%, while the remaining percentage is influenced by other unexamined variables. The Openness variable is the only construct that significantly influences Entrepreneurial Success, while the other four constructs in the independent variables (Emotional Stability, Conscientiousness, Agreeableness, Extraversion) do not show significant effects on Entrepreneurial Success. The researcher found that openness (Openness) to everything faced and anticipated by MSE entrepreneurs, with indicators such as intellect and imagination, is proven to be a key to their success in running a business.